Romantic Analysis in Intizar Hussain Novel, Basti - Sajjad, Saima; Khatak, Sattar (sourcecoder, 2023)
Literature being the perfect reflection of social behavior of any society, no doubt has been bestowed with various genres, and novel is one of the essential portions. This novel portrays the real-life aspects based on reality and true color, in spite of the thought of philosopher’s and intellectuals, the novel covers the very deep themes of politics, region, social and matters related to romance. With the inception of Pakistan, many writers closely associated with literature. Intizar Hussain being one of the prominent literary figures in the realm of Urdu literature focused on the literary techniques, introduced fiction writing, particularly novel. He covered many areas, and the major achievement in this regard was his concentration on theory and, at the same time, the concept of romanticism in the genres of novel. In the novel Basti, he came with the Idea of complete introduction of love and the concept of intimacy, which was presented with superb literary techniques. The novel Basti, the masterpiece of Intizar Hussain, was published in 1980. Hussain’ s work of literature was spontaneous embodiment of love, His art work is the real protraction of his actual creativity and a constant overflow of his rich imagination, the strongest romantic appeal has been presented in his literary efforts.